1996
DOI: 10.2134/jeq1996.00472425002500050012x
|View full text |Cite
|
Sign up to set email alerts
|

Bromide and Nitrogen‐15 Tracers of Nitrate Leaching under Irrigated Corn in Central Nebraska

Abstract: Nitrate leaching from agricultural fields into groundwater has caused environmental and health concerns. A study was conducted during 1992-1993 in the Central Platte Valley of Nebraska to assess the nitrate leaching potential under recommended center-pivot irrigation and fertilizer best management practices for continuous corn (Zea mays L.). At time of planting corn, potassium bromide (KBr) and double-labeled ISN ammonium nitrate (I0 atom% ISNH415NO3) tracers were applied at rates of 200 kg Br ha-i and 30 kg N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 0 publications
0
25
1
Order By: Relevance
“…The sharp reductions in extractable soil inorganic 15 N observed in both experiments (Fig. 7) were immobilized via the intense microbial competition for N in the low N environment, or leached below the sampling depth (Kessavalou et al 1996;Dou et al 2007). …”
Section: Discussionmentioning
confidence: 89%
“…The sharp reductions in extractable soil inorganic 15 N observed in both experiments (Fig. 7) were immobilized via the intense microbial competition for N in the low N environment, or leached below the sampling depth (Kessavalou et al 1996;Dou et al 2007). …”
Section: Discussionmentioning
confidence: 89%
“…For annual crops, the N uptake efficiency is <50%, even when following good management practices (Ju and Zhang, 2003;Gillian et al, 1985) and about 30-50% of applied N fertilizer is leached into groundwater (Zhang, 1987). Using best management practices and near optimum N rates, the amount of NO 3 -N leaching has been estimated to be 41% for irrigated maize (Kessavalou et al, 1996), 32 AE 28% (standard deviation) for irrigated wheat (Ottman et al, 2000) and 27.9% for irrigated Orchardgrass (Watts et al, 1991). In addition, when compared to solely rain-fed fields, the amounts of leached NO 3 -N have been found to be 17 and 53% higher in low and high volume irrigated fields, respectively (Timmons and Dylla, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies [16], we found that the average apparent recovery of N fertilizer by corn grain at the EON rate was 55%, so the 40% lost in leachate in the current study appears to be realistic. Other studies have reported that 41% of applied fertilizer N was lost as leachate in irrigated corn [17] and that 50% of fertilizer N applied to corn was available for leaching, denitrification, and/or NH 3 volatilization [18]. …”
Section: Mass Of Nitrate N Leachedmentioning
confidence: 99%